PTPN2 copper-sensing relays copper level fluctuations into EGFR/CREB activation and associated CTR1 transcriptional repression - Matthew O. Ross; Yuan Xie; Ryan C. Owyang; Chang Ye; Olivia N. P. Zbihley; Ruitu Lyu; Tong Wu; Pingluan Wang; Olga Karginova; Olufunmilayo I. Olopade; Minglei Zhao; Chuan He (Nature Communications, 2024)
Abstract Fluxes in human copper levels recently garnered attention for roles in cellular signaling, including affecting levels of the signaling molecule cyclic adenosine monophosphate. We herein apply an unbiased temporal evaluation of the signaling and whole genome transcriptional activities modulated by copper level fluctuations to identify potential copper sensor proteins responsible for driving these activities. We find that fluctuations in physiologically relevant copper levels modulate EGFR signal transduction and activation of the transcription factor CREB. Both intracellular and extracellular assays support Cu1+ inhibition of the EGFR phosphatase PTPN2 (and potentially PTPN1)–via ligation to the PTPN2 active site cysteine side chain–as the underlying mechanism. We additionally show i) copper supplementation drives weak transcriptional repression of the copper importer CTR1 and ii) CREB activity is inversely correlated with CTR1 expression. In summary, our study reveals PTPN2 as a physiological copper sensor and defines a regulatory mechanism linking feedback control of copper stimulated EGFR/CREB signaling and CTR1 expression.